BaxSr1−xO/MgO nano-composite sorbents for tuning the transition pressure of oxygen: Application to air separation. (1st December 2015) - Jung, Taesung; Na, Jeong-Geol; Cho, Dong Woo; Park, Jong-Ho; Yang, Ralph. T.
Abstract: BaO is a proven oxygen-selective sorbent for air separation via the BaO–BaO2 oxygen sorption–desorption cycle. However, the low transition O2 pressure necessitates a high vacuum that is required for desorption, hence limiting its application. Here, we report facile synthesis of new oxygen-selective Ba x Sr1− x O/MgO nano-composite sorbents from which O2 can be desorbed at moderate vacuum pressures. These sorbents are obtained from Ba x Sr1− x Mg(CO3 )2 precursors synthesized by co-precipitation followed by calcination. It is shown that the transition O2 pressure for the oxide-peroxide cycle is significantly increased by increasing the Sr 2+ /Ba 2+ ratio. XRD results show that the crystal structures are preserved while the lattice constants are reduced upon substitution of Ba 2+ by Sr 2+ in both precursor carbonates and peroxides. Transmission electron microscopy/energy dispersive X-ray spectroscopy results show that Ba 2+ and Sr 2+ are mixed molecularly in Ba x Sr1− x O/MgO nano-composite. We explain that the uniformly substituted Sr 2+ in BaO/BaO2 changes the dissociation energy of peroxide ions and the equilibrium of the reversible reactions, promoting decomposition of BaO2 . Cyclic O2 sorption and desorption with Ba x Sr1− x O/MgO nano-composite is demonstrated. Highlights: O2 -selective sorbents were prepared by calcination of Ba x Sr1− x Mg(CO3 )2 . Uniform distribution and homogeneous mixing of Ba 2+ and Sr 2+ was achieved. Substitution of Ba 2+ by Sr 2+ in Ba x Sr1− x O/MgO sorbents promoted desorption of oxygen. The sorbents hold good potential for lower cost desorption of O2 in vacuum swing sorption.